An Ambulatory Electroencephalography System for Freely Moving Horses: An Innovating Approach - Cousillas, Hugo; Oger, Martial; Rochais, Céline; Pettoello, Claire; Ménoret, Mathilde; Henry, Séverine; Hausberger, Martine (Frontiers in Veterinary Science, 2017)
Electroencephalography (EEG) that has been extensively studied in humans, presents also a large interest for studies on animal brain processes. However, since the quality of the recordings is altered by muscular activity, most EEG recordings on animals are obtained using invasive methods with deeply implanted electrodes. This requires anesthesia and can thus only be used in laboratory or clinical settings. As EEG is a very useful tool for both detecting brain alterations due to diseases or accidents but also to evaluate the arousal and attentional state of the animal, it seemed crucial to develop a tool that would make such recordings possible in the horse’s home environment, with a freely moving horse. Such a tool should not be invasive nor cause discomfort to the horse as the usual other practice which consists, after shaving the zone, in gluing the electrodes to the skin. In order to fulfill these requirements, we developed a novel EEG headset adapted to the horse’s head that allows an easy and fast positioning of the electrodes and that can be used in the home environment on a freely moving horse. In the present study, we show that this EEG headset allows to obtain reliable recordings and we propose an original evaluation of an animal’s “EEG profile” that allows comparisons between individuals and situations. This EEG headset opens new possibilities of investigation on horse cognition and it can also become a useful tool for veterinarians to evaluate cerebral disorders or check the anesthesia level during a surgery.